EFFECTIVENESS OF ULTRASOUND-GUIDED MODIFIED PECTORAL NERVE BLOCK (PECS II) FOR POST-OPERATIVE PAIN RELIEF AFTER MODIFIED RADICAL MASTECTOMY (MRM) - Riaz, Azmat; Saleem, Mudasir; Mahmood, Khalid; Majeed, Kaukab; Hussain, Zaki; Jafri, Asad Ullah (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find the effectiveness of ultrasound guided modified pectoral nerve block (PECS II) versus conventional analgesics for post-operative pain relief in women undergoing modified radical mastectomy.Study Design: Quasi experimental study.Place and Duration of Study: Department of Anaesthesia, Pak Emirates Military Hospital Rawalpindi Pakistan, from May 2018 to Oct 2019.Methodology: A total of 74 adult female patients scheduled for elective unilateral modified radical mastectomy under general anaesthesia were randomized into two groups, pectoral nerve block II (P) group (n=37) and control (C) group (n=37). An ultrasound-guided pectoral nerve block II block was performed using 30 ml of 0.25% Bupivacaine in pectoral nerve block II group after induction of general anaesthesia. In control group (C), patients received only general anaesthesia. Primary outcome measure was opioid consumption in first 24 hours, and the secondary outcome was pain at the breast and axillary region measured using the numerical rating scale (NRS) in first 24 hours at fixed intervals after surgery. Patient satisfaction was evaluated upon discharge using a 4-point scale.Results: Nalbuphine consumption was significantly reduced in pectoral nerve block group as compared to control group. Patients in pectoral nerve block II group experienced much less pain because their numerical rating scale was lower than the control group in postoperative period. Patient satisfaction was found to be high in pectoral nerve block II group.Conclusion: The pectoral nerve block II block is a simple block which provides excellent analgesia for modified radical mastectomy. It can be used for balanced anaesthesia.......